The Effect of Leadership Style and Work Motivation on Employee Performance In Sout Jakarta Publik Accountants - Siska Yunanti (International Journal of Education, Information Technology, and Others, 2023)
This study aims to determine the effect of Leadership Style and Work Motivation on Employee Performance in South Jakarta Public Accountants, to determine the effect of Leadership Style on Employee Performance in South Jakarta Public Accountants, to determine the effect of Work Motivation on Employee Performance in South Jakarta Public Accountants to determine the effect Leadership Style and Work Motivation together on Employee Performance at South Jakarta Public Accountants. The method used in this research is quantitative. The population in this study were all employees with a total of 79 employees. The sample used was 79 respondents with data collection techniques and questionnaires. Methods of data analysis using validity test, reliability test, classic assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. Based on the results of the study, it shows that Leadership Style has an effect on Employee Performance, indicated by the value of tcount = 11.970 while ttable = 1.991 (tcount>ttable). Work Motivation has an effect on Employee Performance with the value of tcount = 14.150 while ttable = 1.991 (tcount>ttable) with a significant level of 0.00 <0.05. Leadership Style and Work Motivation on Employee Performance in South Jakarta Public Accountants where the value of fcount = 120.609 ftable = 3.12 (fcount>ftable) with a significance of 0.000 <0.05. The multiple regression equation is as follows: Y = 3.664 + 0.335 X1 + 0.559 X2 The multiple correlation is 0.872, the test results for the coefficient of determination are 76% and the remaining 24% is influenced by other variables.